Corpo-ateliê: memórias performadas por um professor-artista - Santos, Caue de Camargo dos (2022)
This thesis operates a writing with images and composes blocks of sensations (DELEUZE; GUATTARI, 2010). to produce pathways and make life thrive during this study. The research method used is investigation-creation, which brings out processes that are inscribed in the body, in the face of displacements, experiments, thoughts, places, and in the intersections of bodies, bringing to life existing ways of working with teaching, art and research amidst the intensities of life. It is the record of a body that investigates from memories forged while teaching. In addition, it problematizes what memories can do, or how they return to the body, and what feelings and sensations are provoked in these educational processes. In this way, it starts from a body state in which the artist-teacher thinks about and produces his classes through processes that involve the triggering of memory and creation processes. These ways of existing cross the body of this artist-teacher and trigger the following question: what can a bodystudio of an artist-teacher do when performing through memories? This writing composed with images is affected by the notion of body present in the Spinozist thought (SPINOZA, 2021); the researcher's body is taken by the notion of bodywithout-organs (DELEUZE, 2002) when it is thrown into memories and dragged into a past that extends into the present, thus betting on the concept of memory as duration (BERGSON, 1999). In this way, the experiments carried out in the research produce intersections, which inscribe thoughts and talk about what a body-studio can do when this artist-teacher studies, reads, dances, vibrates, composes, teaches his classes: lives and writes on lines of intensity that intersect this investigation-creation and instigates the body to want to experiment,reach limits and forge new combinations in the face of exhaustion (DELEUZE, 2010). In the area of education and art, when dealing with 'the data' of memory and experience, added to this philosophical scope of time, it is possible to compose plans, instances and ways of thinking and problematizing the curriculum, the class, the students' production, compose another organicity in the time-space of the class.